2005
DOI: 10.1074/jbc.m502463200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Agonist-independent Association of Human Peroxisome Proliferator-activated Receptors with Coactivators

Abstract: Lipid homeostasis is controlled by various nuclear receptors (NRs), including the peroxisome proliferatoractivated receptors (PPAR␣,␦

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 65 publications
4
57
1
1
Order By: Relevance
“…It has previously been proposed that PPARs have high basal activity because of a ligand-independent stabilization of helix 12 in the LBD, resulting in ligand-independent coactivator association (Molnar et al, 2005). Although this could in principle explain the inverse agonistic properties of ST247, this is unlikely, because we were unable to detect changes in CBP recruitment to the ANGPTL4 gene upon ST247 treatment (data not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…It has previously been proposed that PPARs have high basal activity because of a ligand-independent stabilization of helix 12 in the LBD, resulting in ligand-independent coactivator association (Molnar et al, 2005). Although this could in principle explain the inverse agonistic properties of ST247, this is unlikely, because we were unable to detect changes in CBP recruitment to the ANGPTL4 gene upon ST247 treatment (data not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…However, the AF2 of the ligand binding domain (LBD) may also contribute to the ligand-independent transactivation. Helix 12 has been reported to be in an "agonist position" in crystal structures of apo-PPAR␥LBD (46), and recent investigations indicated that this is due to the stabilization of helix 12 in the agonist position by specific charged amino acids in the LBD (42). In keeping with this, PPAR␥LBD has recently been shown to interact with CBP/p300 (33) as well as p160 CoA (42) in the absence of ligands.…”
Section: Discussionmentioning
confidence: 54%
“…Helix 12 has been reported to be in an "agonist position" in crystal structures of apo-PPAR␥LBD (46), and recent investigations indicated that this is due to the stabilization of helix 12 in the agonist position by specific charged amino acids in the LBD (42). In keeping with this, PPAR␥LBD has recently been shown to interact with CBP/p300 (33) as well as p160 CoA (42) in the absence of ligands. Presence of a synthetic ligand further induces stabilization of helix 12, thereby leading to an increased interaction with coactivators (42).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Binding of a ligand with agonistic properties to the nuclear receptors causes a conformational change within their ligand-binding domain that results in the replacement of co-repressors by co-activator proteins, such as receptor-associated co-activator 3 (16) or PPAR␥ co-activator 1␣ (PGC-1␣) (17). These co-activators link ligand-activated nuclear receptors to enzymes displaying histone acetyltransferase activity that cause chromatin relaxation and thereby reverse the action of unliganded nuclear receptors.…”
mentioning
confidence: 99%